Hydroacoustic Data‐Analysis Recommendations to Quantify Prey‐Fish Abundance in Shallow, Target‐Rich Ecosystems. (19th February 2019) - Dillon, Rebecca A.; Conroy, Joseph D.; Ludsin, Stuart A.
Abstract: Standardized sampling methods can benefit fisheries management by facilitating a comparison of fish abundance estimates within and among ecosystems. Towards developing an improved standardized hydroacoustic method for estimating prey‐fish abundance and target strength in small (surface areas <15 km 2 ), shallow (maximum depths <20 m), freshwater ecosystems (e.g., north‐temperate reservoirs), we evaluated how the incorporation of several recommended hydroacoustic data‐analysis procedures from the Great Lakes Standard Operating Procedures (GLSOP) into an existing hydroacoustic protocol used in north‐temperate reservoirs influenced estimates of prey‐fish abundance. To facilitate our evaluation, we conducted hydroacoustic surveys in four Ohio reservoirs during August 2016 and then compared prey‐fish abundance estimates generated from the existing Ohio Department of Natural Resources, Division of Wildlife reservoir protocol with those that included three GLSOP recommendations separately and in combination. The three recommendations were (1) removal of background noise, (2) use of a lower maximum beam compensation (MBC) setting, and (3) application of the Sawada index (Nv ) to identify and replace biased, in situ, cell‐specific target strengths. Our analyses showed that the removal of background noise (−0.1% to 0% change) and application of Nv (−7.8% to 0% change) had little substantive effect. However, decreasing the MBC from 12 to 6 dB significantly reduced prey‐fish abundance estimates (4.1% to 16.1% decrease). When we simultaneously applied all three GLSOP recommendations, estimated prey‐fish abundance consistently decreased (−8.8 to −16.0%) across reservoirs. Collectively, our findings suggest the need for incorporation of several GLSOP data‐analysis procedures into protocols developed for shallow, target‐rich ecosystems, such as Ohio reservoirs. By doing so, more precise estimates of fish abundance can be generated to the benefit of fisheries management.